Penggunaan Pupuk Organik untuk Peningkatan Produktivitas Daun Murbei (Morus sp.) Sebagai Pakan Ulat Sutera (Bombyx mori L.) - Wiwit Setiadi; Kasno Kasno; Noor Farikhah Haneda (Jurnal Silvikultur Tropika, 2011)
Utilization of Organic Fertilizer to Productivity Mulberry (Morus alba) Leaf’s Quality as Silkworm (Bombyx mori) FeedOne of effort, to obtain maximum cocoon production by feeding silkworms with mulberry leaves are sufficiant. Fertilizing by using organic fertilizer was one of effort to improve mulberry productivity. Organic fertilizer used in this research was animal manure, liquid organic fertilizer and compost. Measurement of parameters of mulberry productivity were leaf total, leaf weight, leaf area, plant height, branch length, and branch total; while observed parameters of silkworm cocoon quality were mortality percentage, cocoon weight, cocoon skin weight, cocoon skin percentage, and cocoon quality class.ANOVA test result shows that application fertilizers has an insignificant effect to leaf total, leaf weight, plant height, and branch length. Treatment by using a liquid organic fertilizer had the highest values for all parameters measured. Adversely, fertilizing has a significant effect to leaf area, branch total, cocoon weight, cocoon skin weight and cocoon skin percentage. Highest mortality percentage was resulted from control treatment that was amounted 13.75%; while lowest mortality percentage was resulted from compost fertilizer treatment that amounted 4.75%. Highest cocoon weight, cocoon skin weight and cocoon skin percentage was resulted from animal manure treatment. Best cocoon quality was B class for control, animal manure and liquid organic fertilizer, while for treatment using compost fertilizer has a C class cocoon quality. In an outline granting manure, liquid organic fertilizer and fertilizer compost sequentially give increase production of leaves at 2,39 tons/ha, 3,49 tons/ha and 2,94 tons/ha.Fertiler application by using liquid organic fertilizer produced highest profit, which amounted Rp.2.672.900, compared with normal income (without fertilizing) after reduced by production cost and other expenditures such as fertilized and fertilizing application cost (detail attached).